Zwitterions coated hollow fiber membranes with enhanced antifouling properties for osmotic power generation from municipal wastewater. (1st November 2016) - Zhao, Dieling; Qiu, Guanglei; Li, Xue; Wan, Chunfeng; Lu, Kangjia; Chung, Tai-Shung
Abstract: Fouling on pressure-retarded osmosis (PRO) membranes leads to severe declines in water flux and power density because their porous substrates are facing the wastewater feed. Thus, inorganics, organics and microorganisms in the wastewater are prone to depositing on the substrate surface and even in its pores. In order to reduce the fouling propensity, coating the substrate surface of PRO membranes with zwitterionic materials proves to be an effective way. In this work, 2-methacryloyloxyethylphosphorylcholine (MPC), is modified and grafted onto the polydopamine (PDA) coated poly (ether sulfone) (PES) hollow fiber substrate. Both the synthesis and surface coating of MPC are easy and facile to be scaled up. Compared with the pristine PES and PES-PDA substrates, the MPC modified substrate (PES-PDA-MPC) exhibits high resistance to protein adsorption as well as bacteria adhesion. By using a state-of-the-art thin-film composite poly (ether sulfone) (TFC-PES) hollow fiber membrane as the control for power generation, the power density of the TFC-PES-PDA-MPC membrane can achieve as high as 7.7 W/m 2 while the unmodified one has only 6.0 W/m 2 after 3 h's PRO tests. In conclusion, the osmotic power generation of PRO membranes can be significantly sustained by modifying the membrane surface with zwitterions. Graphical abstract: Highlights: A Zwitterion coated pressure osmosis retarded (PRO) membrane was developed. It exhibited high resistance to protein adsorption and bacteria adhesion. It showed good antifouling properties with a higher sustainable power density. Wastewater from municipal recycle plant was employed as feed for power generation.